The Effect of Incentivized Electronic Word-of-Mouth (EWOM) on Consumer Purchase Intention - Muhammad Husni Tamrin; Nurul Huda (Universitas Islam Nahdlatul Ulama Jepara, 2021)
Objective: Social media has a strong impact as a reference for consumers in getting information about the product. Electronic word-of-mouth (eWOM), which is usually delivered by social media, is still the most secure advertising media. This study provides information about incentivized eWOM on purchase intention and other factors that can affect consumers. Research Design & Methods: The method used in this research is the quantitative method with an associative approach. Descriptive analysis and structural equation modeling were used to measure the influence of these variables. Findings: The results showed that the incentivized eWOM had a significant effect on purchase intention but had no impact on the company’s brand awareness. Meanwhile, the attractiveness of advertising messages has no significant effect in influencing purchase intention but has a significant effect on the company’s brand awareness. Implications & Recommendations: Although this research give contributions to the e-WOM literature, several limitations and future research suggestion deserve mentions. Further research can examine the relative effectiveness of non-monetary incentives. Contribution & Value Added: Researchers have provided input and suggestions to SMEs to optimize incentivized eWOM to increase consumer purchase intention.